“This sense of otherness”: The Horrors of the Countryside in Andrew Michael Hurley’s Starve Acre. - Mercer E (Taylor and Francis Group, 2024)
In novels The Loney (2014), Devil’s Day (2017) and Starve Acre (2019), contemporary British author Andrew Michael Hurley locates threat in the British countryside where primitive superstition continues to exist. Describing his writing as “folk horror,” Hurley tempers nostalgic desires for a traditional rural lifestyle by revealing its barbaric underpinnings. In his most recent novel, he also critiques contemporary values. In Starve Acre, the Willoughby family are tormented by superstitious beliefs, but they are ultimately undone by a privileging of material secular realities. Starve Acre thus represents the traditions of the rural past and those of the urban present as equally threatening. This bleak vision of British life suggests that solace is not to be found in idealized notions of an escape from contemporary living to the traditional lifestyles of the past. Rather, that the return to a life lived in harmony with the environment must be accompanied by a psychic return that acknowledges the power and fundamental otherness of nature. What Hurley’s fiction highlights is that the anti-Enlightenment project associated with Gothic’s varied manifestations, including folk horror, can be harnessed for contemporary concerns with how humanity might better exist in and relate with the natural environment.